2019
DOI: 10.1097/jpo.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Does the Application of a Lycra Arm Sleeve Change Shoulder Biomechanics in Young Healthy People? A Mechanistic Study

Abstract: Background/Aims: Glenohumeral subluxation (GHS) is commonly reported in people with stroke. Lycra sleeves provide a compressive and supportive effect, influencing the neuromuscular activity in the affected body segment. A recent study reported reduction in GHS (acromion-greater tuberosity (AGT) distance) following application of Lycra arm sleeve, however, its mechanism on the shoulder region as a whole is unclear. The aim of this study was to investigate if application of a Lycra sleeves changes the AGT distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 31 publications
2
4
1
Order By: Relevance
“…A study that explored the effect of kinesiology taping on HSP showed significant improvement in EMG activity in deltoid and supraspinatus muscle, implying that kinesiology taping can activate the muscles 33 . This is in agreement with a previous study on young able-bodied participants (n = 30) that reported a similar slight increase in muscle activity 20 . In all the studies including ours, surface electrodes were used.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…A study that explored the effect of kinesiology taping on HSP showed significant improvement in EMG activity in deltoid and supraspinatus muscle, implying that kinesiology taping can activate the muscles 33 . This is in agreement with a previous study on young able-bodied participants (n = 30) that reported a similar slight increase in muscle activity 20 . In all the studies including ours, surface electrodes were used.…”
Section: Discussionsupporting
confidence: 91%
“…Application of the Lycra sleeve resulted in mean reduction in the AGT distance (mean, 0.13 cm) when compared with the distance before application of the sleeve; however, this was not statistically significant. In contrast, previous studies on people with chronic stroke (n = 5) 19 and young able-bodied population (n = 31) 20 showed a statistically significant mean reduction of 0.24 cm and 0.12 cm, respectively, immediately after the application of sleeve. This could be attributed to differences in methodology.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations